Tectonics and sedimentation of early continental collision in the Eastern Mediterranean (Northwest Syria). - Hardenberg, Mathew F (University of Edinburgh; College of Science and Engineering; School of GeoScience, 2004)
The northeastern margin of the African plate, in the Latakia region of northwest Syria, has an important bearing on the closure and collisional history of the Tethys Ocean in the Eastern Mediterranean region. This field-based study focuses on the Tertiary geology of the Nahr El-Kabir basin and provides new insights on the sedimentation, biochronology, structure and regional tectonics of the area. Three unconformity-bound megasequences of Late Cretaceous to Tertiary age are identified, which were strongly influenced by tectonic processes: 1. Late Maastrichtian-Mid Eocene; 2. Miocene; 3. Late Miocene (Messinian)-Late Pliocene. Megasequence 1 was initiated by a Late Maastrichtian-age marine transgression over Maastrichtian-emplaced ophiolitic rocks and melange (Baer Bassit Massif). Water depths increased in the Palaeocene, giving rise to outer-shelf-depth carbonate deposition, rich in planktic foraminifera. Marine high productivity is reflected in common diagenetic chert formation. Nummulite-rich carbonates accumulated on a shallower shelf during Early-Mid Eocene time. Shallowing of marine conditions, coupled with tectonic instability, culminated in emergence, followed by a Late Eocene-Oligocene hiatus. Megasequence 2 is spatially restricted to the Nahr El-Kabir Graben and begins with Early Miocene carbonate deposition of mainly pelagic facies. In the Middle Miocene, there was an increasing input of basin margin-derived high-density turbidites and debris flows. Minor ongoing tectonism was followed by regression during the Messinian salinity crisis. Megasequence 3 begins with the accumulation of mainly laminated gypsum, followed by gypsum debris flows and selenitic gypsum. Initial Pliocene transgression led to shallow-marine, open-shelf muddy sedimentation, shallowing up, prior to the Late Pliocene into marls and bioclastic carbonates. Late Pliocene-Quaternary time was marked by progressive uplift, marine and continental terracing and erosion. A Maastrichtian to Paleogene submerged shelf succession on the Arabian Platform culminated in a regional hiatus during the Late Eocene-Oligocene. Early Neogene rifting led to development of a transtensional basin (the Nahr El-Kabir Graben, a probable half graben). Strike-slip deformation (probably sinistral) and regional uplift followed during Late Neogene-Quaternary time. The Miocene Nahr El-Kabir Graben developed along an important, inferred, transform fault system. The resulting El-Kabir Lineament demarcates the northern margin of the African Plate (Arabian sub-plate). The El-Kabir Fault links southwestwards with the southern Cyprus active margin and northeastwards with the Dead Sea Transform Fault and, thus, represents an important, previously unrecognised, segment of the Africa-Eurasia plate boundary.